Human Resources for Cancer Control in Uttar Pradesh, India: A Case Study for Low and Middle Income Countries - Daphtary, Maithili; Agrawal, Sushma; Vikram, Bhadrasain (Frontiers in Oncology, 2014)
For addressing the growing burden of cancer in low and middle income countries an important first step is to estimate the human resources required for cancer control in a country, province or city. However, few guidelines are available to decision-makers in that regard. Here we propose a methodology for estimating the human and other resources needed in the state of Uttar Pradesh (UP), India as a case study. Information about the population of UP and its cities was obtained from http://citypopulation.de/. The number of new cancer cases annually for the commonest cancers was estimated from GLOBOCAN 2008 (http://globocan.iarc.fr). For estimating the human resources needed the following assumptions were made: newly diagnosed cancer patients need pathology for diagnosis and for treatment surgery, chemotherapy, and/or radiotherapy. The percentage of patients requiring each of those modalities, their average lengths of stay as in-patients, and number of in-patient oncology beds were estimated based upon expert opinions. The resources already available in UP were determined by a telephone survey and by searching the websites of radiation therapy centers and medical colleges. Twenty-four radiation oncologists at 21 cancer centers in ten cities responded to the survey. As detailed in this manuscript, an enormous shortage of human resources for cancer control exists in UP. Human resources are the key to diagnosing cancers early and treating them appropriately. Addressing the shortage will not be easy but we hope that the methodology described here can guide decision-makers and form a framework for discussion among the various stakeholders. This methodology is readily adaptable to local practices and data.